JENIS KUPU-KUPU DI BERBAGAI TIPE HABITAT PADA KAWASAN HUTAN LINDUNG AMBAWANG DESA SUNGAI DERAS KECAMATAN TELUK PAKEDAI KABUPATEN KUBU RAYA - Rahman, Aryf; Kartikawati, S M; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2018)
This study aims to the species of butterflies based on habitat type in Ambawang protected forest area, Sungai Deras village, Kubu Raya. The research method, that is explore the distribution of butterfly on 3 habitat type accordance with morning and evening activity. The data taken were species and quantity of butterfly which arrest and direct observation. Butterfly samples arrested made insectarium to facilitate identification. The result showed 17 genus of butterflies. Butterfly that often founded in 3 mullet were Neptis, Vindula, dan Moduza. While, in the secondary forest found most genus is Graphium, Papilio, Neptis, Vindula, Lexias, Tanaecia sp1, Moduza, Tanaecia sp2, Euploea, Charaxes, Acytolepis, dan Taxila.Keyword: Ambawang protected forest, butterfly, habitat.